Direct nephrotoxic effect of Sri Lankan Russell's viper venom – an experimental study using in vitro models - Gunatilake, Mangala; Jayakody, R.L.; Angunawela, P.; De Tissera, A. (Faculty of Medicine, University of Colombo, 2002)
Nephrotoxicity manifesting as acute renal failure is the principal cause of death in Russell's viper envenomation. The mechanisms responsible for nephrotoxicity are not clear and lack of experimental data in the Sri Lankan context prompted us to do this study. In the present experiments, the time related physiopathological changes in rabbits after injection of Russell's viper venom were studied using two in vitro models, viz. the isolated perfused kidney model and the kidney slice model. The isolated perfused kidney model experiments showed a significant time related reduction in renal function 4 hours after envenomation. This was associated with disturbances to the renal tubular cell integrity and renal pathology. Experiments using venom on kidney slices showed complete necrosis of the glomeruli and proximal convoluted tubular cells with the preservation of the basement membranes of tubular cells suggestive of direct damage caused by the venom. Data from these experiments are highly suggestive that Russell's viper venom causes renal damage mainly by a direct action on the kidney.
Keywords: Russell's viper venom; Renal failure; Direct nephrotoxicity; Isolated perfused kidney model; Kidney slice model